Spoliation and exception in brazilian metropolises: the PAC case in the metropolitan region of Rio de Janeiro - Thiago Oliveira Lima Matiolli; Ana Carolina Christovão (Revista Produção e Desenvolvimento, 2015)
This paper presents a reflection that is the result of a survey which intended to monitor the works of the Growth Acceleration Program (PAC) in the Metropolitan Region of Rio de Janeiro (RMRJ). After two years of research and from this empirical object, we intend to think the management of Brazilian cities over the past decade in the context of the Lula Government, in particular, whose performance is considered in a discussion about the possibility of a New-Developmentalism, since this government is marked by a strong presence of the state in the construction of economic infrastructure and efforts to combat social inequalities.